2011
DOI: 10.1149/1.3562204
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Pattern Size Dependence of Copper Corrosion in Submicron-Scale Features

Abstract: The effects of grain size and pattern geometry on the etching rate were investigated by using our invented pattern, and each pattern has a same height of electrodeposits regardless of pattern size after electroplating. It was found out that the logarithmic value of the etching rate is inversely linear with the pattern width at self-annealed specimen. In other words, as the pattern width decreases, the etching rate increases exponentially. Such tendency of the etching rate is owing to the result that the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…6. [17][18][19][20][21] Figure 7 shows the high resolution transmission electron microscopy (TEM) image for the sample of Ni 2 s/Pd 30 s, and it was reconfirmed that the Pd nuclei had a size of about 3 ∼ 5 nm. We could discern the lattice fringes of the Cu (111), Ni (111), and Pd (111) planes by their interplanar spacings of 0.2083, 0.2031, and 0.2242 nm, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…6. [17][18][19][20][21] Figure 7 shows the high resolution transmission electron microscopy (TEM) image for the sample of Ni 2 s/Pd 30 s, and it was reconfirmed that the Pd nuclei had a size of about 3 ∼ 5 nm. We could discern the lattice fringes of the Cu (111), Ni (111), and Pd (111) planes by their interplanar spacings of 0.2083, 0.2031, and 0.2242 nm, respectively.…”
Section: Resultsmentioning
confidence: 88%
“…A geometric constraint in the patterned space is expected to affect the grain growth behavior. [3][4][5] It has been reported that when microstructures of different sizes are formed depending on geometrical constraints in the pattern space, electrochemical reaction characteristics, such as galvanic corrosion are also affected. 5 In addition, Janus Green B (JGB), one of the levelers used to suppress bump formation by the curvature enhanced accelerator coverage (CEAC) phenomenon of the plating accelerator, is adsorbed on the surface of the electrodeposits resulting into co-deposition inside the electrodeposits.…”
mentioning
confidence: 99%
“…[3][4][5] It has been reported that when microstructures of different sizes are formed depending on geometrical constraints in the pattern space, electrochemical reaction characteristics, such as galvanic corrosion are also affected. 5 In addition, Janus Green B (JGB), one of the levelers used to suppress bump formation by the curvature enhanced accelerator coverage (CEAC) phenomenon of the plating accelerator, is adsorbed on the surface of the electrodeposits resulting into co-deposition inside the electrodeposits. In our previous experiment in which the concentration of JGB was changed from 0 to 1 mM, it was found that the impurity concentration of the plating layer was proportional to the concentration of JGB added to the plating solution, and recrystallization was suppressed at a concentration of 0.2 mM or more.…”
mentioning
confidence: 99%